2017
DOI: 10.1080/08897077.2016.1275927
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Competent Opioid Prescribing Education: Increasing Dissemination with a Train-The-Trainer Program

Abstract: Background: Due to the high prevalence of prescription opioid misuse, the US Food and Drug Administration (FDA) mandated a Risk Evaluation and Mitigation Strategy (REMS) requiring manufacturers of extended-release/long-acting (ER/LA) opioids to fund continuing education based on an FDA curricular Blueprint. This paper describes the Safe and Competent Opioid Prescribing Education ( SCOPE of Pain) train-the-trainer program and its impact on (1) disseminating the SCOPE of Pain curriculum and (2) knowledge, confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Other strategies described in the literature include brief one-on-one physician education, 311,312 development and dissemination of guidelines and policies, 313,314 and Risk Evaluation and Mitigation Strategy. 315 Public health detailing is an approach based on the pharmaceutical sales strategy, by which messages are pushed using brief one-on-one educational visits during the normal workflow. Staten Island saw a reduction in high-dose prescribing and stabilizing of days' supply after implementing this strategy.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other strategies described in the literature include brief one-on-one physician education, 311,312 development and dissemination of guidelines and policies, 313,314 and Risk Evaluation and Mitigation Strategy. 315 Public health detailing is an approach based on the pharmaceutical sales strategy, by which messages are pushed using brief one-on-one educational visits during the normal workflow. Staten Island saw a reduction in high-dose prescribing and stabilizing of days' supply after implementing this strategy.…”
Section: Recommendationsmentioning
confidence: 99%
“…318 The SCOPE of Pain program has also implemented a “train the trainer” approach, which facilitates wide dissemination of information. 315 Physicians are advised to be aware of potential conflicts of interest when attending pharmaceutical company–funded sessions. 319…”
Section: Recommendationsmentioning
confidence: 99%
“…The REMS program has potential to improve the safety of using opioids for the treatment of chronic pain . The Safe and Competent Opioid Prescribing Education (SCOPE of Pain) program was also implemented within the REMS framework . It was demonstrated that using this program has resulted in improvements in knowledge, attitudes, confidence, as well as in safer opioid prescribing practices.…”
Section: Discussionmentioning
confidence: 99%
“…31 The Safe and Competent Opioid Prescribing Education (SCOPE of Pain) program was also implemented within the REMS framework. 31,32 It was demonstrated that using this program has resulted in improvements in knowledge, attitudes, confidence, as well as in safer opioid prescribing practices. This program contributed greatly to stopping or even reversing the trend of increasing rates of opioid abuse, addiction, overdose, and death observed prior to implementation of the REMS.…”
Section: Study Implicationsmentioning
confidence: 99%
“…Current online and in‐person educational sessions address the medical knowledge that physicians need and want when it comes to prescribing opioids. For example, one of the more effective educational strategies for modifying physician prescribing is the “academic detailing” using a “train‐the trainer” system . The effectiveness of detailing, modeled on “drug detailing” visits to physicians by pharmaceutical representatives, is largely due to its face‐to‐face delivery of an individualized educational session with up‐to‐date information on best practices in opioid prescribing.…”
Section: Recommendationsmentioning
confidence: 99%